2019
DOI: 10.1002/zoo.21467
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and solutions: An analysis of community‐reported needs of AZA collaboratively managed animal populations

Abstract: Zoos and aquariums accredited by the Association of Zoos and Aquariums (AZA) cooperatively manage Species Survival Plan (R) (SSP) Program populations to maximize genetic and demographic health and work toward long-term population sustainability.However, recent analyses suggest that only a minority of populations were projected to maintain their sustainability goals over 100 years. As one of the initial steps in addressing this concern, the AZA collaborated with hundreds of members of the zoo and aquarium commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…While we found that climatic variables in general play a limited role in determining captive reproductive success, high annual rainfall negatively with reproductive success, consistent with King (2008). We more detailed assessments incorporating seasonality and photoperiod to potentially reveal more nuanced relationships not identified here (Wilson et al, 2019).…”
Section: Temporal Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…While we found that climatic variables in general play a limited role in determining captive reproductive success, high annual rainfall negatively with reproductive success, consistent with King (2008). We more detailed assessments incorporating seasonality and photoperiod to potentially reveal more nuanced relationships not identified here (Wilson et al, 2019).…”
Section: Temporal Patternsmentioning
confidence: 99%
“…However, this popularity has also made it clear that certain institutions are reluctant to relocate their flamingos to other institutions (King & Bračko, 2014). In addition, limited space, lack of standardized husbandry practices, and the need for improved fulfillment of breeding and transfer recommendations all pose significant problems for currently managed ex situ populations (Wilson et al, 2019). Nearly 40% of AZA co-operatively managed colonial bird breeding programs state that they require additional space if population sustainability goals are to be met (Wilson et al, 2019).…”
Section: Temporal Patternsmentioning
confidence: 99%
“…The development of PMCTrack in 2008 by the Lincoln Park Zoo has enabled the AZA community to have a better understanding of how well zoos and aquariums are following the breeding and transfer recommendations issued by SSPs, which are the short‐term actions needed to guide populations towards long‐term viability (see Faust, Long, Perišin, & Simonis, this issue). More recent examples within AZA are population viability analyses (PVAs), which have been conducted for a number of species (see Che‐Castaldo et al, this issue), and an SSP Sustainability Database that was created to collate data for each SSP Program on population status, husbandry challenges, research needs, and sustainability action required (see Wilson, Dorsey, & Moore, this issue). All of these efforts aimed to clarify the sustainability challenges for individual managed programs so that individual facilities could take actions to align their resources with SSP Program needs to enhance the viability of their populations.…”
Section: Efforts To Address the Sustainability Crisismentioning
confidence: 99%
“…Although all facilities may have species that are not SSP Programs but are held because of their own regional, taxonomic, or other priorities, these facilities should reflect on the proportion of their collection that is in unmanaged programs compared to SSP Programs. Using RCPs, along with other resources such as the SSP Sustainability Database (see Wilson et al, this issue), to guide an institution's ICP processes and decisions ensures that the community is working together to further shared priorities and avoids allocating significant resources to species that are not association‐wide priorities. McCann and Powell's analysis (this issue) shows that at least for some mammalian taxa, facilities are generally aligned with RCPs, but there is room for improvement that could help many non‐viable populations.…”
Section: Efforts To Address the Sustainability Crisismentioning
confidence: 99%
“…In response to the recent AZA sustainability database (AZA SSP® Sustainability Database; see also Wilson, ) category “Research Opportunities”, 63 Species Survival Plans® listed “Behavior” as an area of concern in need of research to improve population sustainability. However, of those, only four specified a need for “mate choice” research, suggesting that more information about the potential contribution of choice for improving mate compatibility is warranted.…”
Section: Introductionmentioning
confidence: 99%